2014
DOI: 10.19030/ajee.v5i2.8953
|View full text |Cite
|
Sign up to set email alerts
|

An Engineering Learning Community To Promote Retention And Graduation Of At-Risk Engineering Students

Abstract: Retention and graduation rates for engineering disciplines are significantly lower than desired, and research literature offers many possible causes. Engineering learning communities provide the opportunity to study relationships among specific causes and to develop and evaluate activities designed to lessen their impact. This paper details an engineering learning community created to combat three common threats to academic success of engineering students: financial difficulties, math deficiencies, and the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Meeting these psychological needs appears to be essential for optimal functioning of the natural tendency for growth and integration, as well as for constructive social development and personal well-being (Ryan & Deci, 2000b). Moreover, recent studies suggest that a sense of belonging to the engineering community and social integration (both peer-to-peer and student-to-faculty) improve student retention, which is a big concern in the engineering education community (Butterfield & Branch, 2016;Marra, Chia-Lin, Bogue & Pytel, 2015;Marra, Rodgers, Shen & Bogue, 2012;Ricks et al, 2014;Tuchscherer, Gray & Gray, 2017).…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…Meeting these psychological needs appears to be essential for optimal functioning of the natural tendency for growth and integration, as well as for constructive social development and personal well-being (Ryan & Deci, 2000b). Moreover, recent studies suggest that a sense of belonging to the engineering community and social integration (both peer-to-peer and student-to-faculty) improve student retention, which is a big concern in the engineering education community (Butterfield & Branch, 2016;Marra, Chia-Lin, Bogue & Pytel, 2015;Marra, Rodgers, Shen & Bogue, 2012;Ricks et al, 2014;Tuchscherer, Gray & Gray, 2017).…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…Corroborating the findings of Ricks et al 5 , learning communities have been commonly identified as a strategy to provide tools for these populations 2,7,8,9,10 . Coston et al 10 determined that students "solved problems, studied together, shared texts and called each other for support in many areas of their lives", and thus managed to overcome multiple "stressors" that effect the success of underrepresented students in transferring from a two-year community college and subsequently completing a four-year degree.…”
Section: Introductionmentioning
confidence: 95%
“…Increasing the numbers of successfully graduating minority students in Science, Technology, Engineering and Math (STEM) is known to be achieved by intentional strategies to recruit students to and retain students at community colleges: emphasizing dual credit classes in high school, providing opportunity for career related experiences and providing community-related support 4 . Other research showed that financial difficulties and math deficiencies, in addition to a lack of belonging to the engineering communities, were barriers to success 5 . Similarly, Soria 6 determined that socioeconomically disadvantaged students struggled more with integration on campus compared to their middle and upper class peers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inception of S-STEM program, universities and colleges across the country have received support from this program through a competitive process [4][5][6][7][8] . The literature shows that the S-STEM program has generated positive impacts in undergraduate STEM education [4][5][6][7][8] . For example, Kalevitch et al created a Living-Learning Cohort model for the S-STEM students at their university 6 .…”
Section: Introductionmentioning
confidence: 99%